The Role of the Tahfizh Al-Quran Islamic Boarding School’s Management in Advancing the Province of Jambi’s Educational Vision and Mission - Darmansyah, Rafik; Ritonga, Ahmad Husein; Arifullah, Mohd (Journal of Social Work and Science Education, 2024)
The purpose of this study is to (a) comprehend how the Tahfizh Islamic Boarding School’s administration developed its educational vision and objective. (b) to identify the motivating and impeding elements; (c) to disclose initiatives aimed at enhancing the administration of the Tahfizh al-Qur’an Islamic Boarding School. This study used a descriptive-analytical approach that was divided into three stages: theoretical explanation, field fact description, and examination of the fit between theory and practice. Techniques for gathering data include documentation, interviews, and observation. The Miles and Huberman model is used in data analysis, while data triangulation is used in data validity procedures. The study discovered that Tahfizh Islamic boarding schools’ management, from planning and organizing to implementing and supervising, has not optimally adhered to contemporary management principles. This is evident in the lack of readily available, factual planning, organizing, management, and supervision documents. Supporting factors include a) the academic community’s high degree of openness to students; b) the teachers’ abilities; c) the teachers' role in imparting knowledge and the muaddib’s role in transforming it; d) the kiai’s role in providing round-the-clock supervision for students; e) the leader’s significant influence and some members of the public’s trust; and f) the academic community’s shared commitment. The fact that funding is scarce and infrastructure is still missing is an impediment. By hosting Tahfiz Al-Qur’an graduations, efforts are being made to enhance the administration of Islamic boarding schools that follow the Tahfizh Qur’an and to further the goals and objectives of education in the province of Jambi. Every year, there is a tahfizh Al-Qur’an graduation, which encourages students to build their educational vision and mission by arranging competitions amongst themselves and by having them participate in MTQ. The Tahfizh Qur’an Islamic boarding school also attempts to fill in time management, recitations, and imam scheduling.